Comparing the use of space in selfies on Chinese Weibo and Twitter. Issue 2 (June 2017) - Roberts, Jessica; Koliska, Michael
Selfies are a ubiquitous practice worldwide in which social media users create and share cultural artifacts that go beyond mere idealized or narcissistic self-presentations. As a cultural phenomenon, selfies reflect not just personal impressions but also communal values of modern life. This study analyzes the use of place in selfies as a defining visual element of self-representation in the United States and China. In particular, this research examines differences and commonalities in the places used to create meaning in selfies in the two national contexts. Our research shows that the deliberate use of places plays a critical role in the presentation of self within selfies both in the United States and China. While there are significant differences in some aspects of selfie construction, the selection of places for selfies followed similar patterns of public and private spaces in both countries, privileging the domestic and commercial most of all, and providing some support for the dominance of a global online culture over the influence of a specific national culture in presentations of the self.